Redesign Identitas Visual Batik Murni Madiun sebagai Upaya Meningkatkan Brand Awareness - Alfina Zalfa Maharani; Aditya Rahman Yani; Sri Wulandari (Lembaga Pengembangan Kinerja Dosen, 2025)
Batik Murni Madiun is a production place for batik motifs typical of Madiun City. However, the low brand awareness of the Batik Murni Madiun brand is a major challenge due to the lack of consistent visual identity. This design aims to redesign the visual identity that can increase brand awareness. This design uses qualitative and quantitative data collection methods with primary data coming from interviews, observations and questionnaires. Meanwhile, secondary data comes from books, journals, and articles. The data analysis technique used in this design is descriptive analysis and TOWS matrix. The data analysis process resulted in the keyword “Madiun Authentic Traditional Batik” which will be used as a reference in making the design concept. In addition, the results of the data analysis show the need for a visual identity that has the philosophy and image that Batik Murni Madiun wants to highlight, namely the authentic traditional batik motifs from Madiun City and the natural colors used for its batik products. Through this visual identity redesign, it is expected to increase brand awareness and build consumer confidence in Batik Murni Madiun through the image that will be shown.